2008
DOI: 10.1086/588567
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Methicillin-Resistant Staphylococcus aureus (MRSA) Acquisition in Roommate Contacts of Patients Colonized or Infected With MRSA in an Acute-Care Hospital

Abstract: Roommates of patients with MRSA are at significant risk for becoming colonized. Further study is needed of the impact of hospital antimicrobial formulary decisions on the risk of acquisition of MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 37 publications
2
27
1
1
Order By: Relevance
“…Similarly, we showed that covered wounds or skin lesions protect significantly against transmission of MRSA from index persons to their household contacts. This is contrary to the results of a study by Moore et al showing that broken skin or chronic skin lesions contribute to the acquisition of MRSA in roommate contacts with MRSA colonization or infection (25). We assume that in our setting, due to strict aseptic wound care, including proper coverage of wounds and hygienic precautions, the risk of MRSA transmission may be significantly lowered.…”
Section: Discussioncontrasting
confidence: 77%
“…Similarly, we showed that covered wounds or skin lesions protect significantly against transmission of MRSA from index persons to their household contacts. This is contrary to the results of a study by Moore et al showing that broken skin or chronic skin lesions contribute to the acquisition of MRSA in roommate contacts with MRSA colonization or infection (25). We assume that in our setting, due to strict aseptic wound care, including proper coverage of wounds and hygienic precautions, the risk of MRSA transmission may be significantly lowered.…”
Section: Discussioncontrasting
confidence: 77%
“…Die Übertragungswahrscheinlich-keit korreliert mit Faktoren, die die Freisetzung bzw. Einwirkung beeinflussen, dem Kolonisationsdruck (d. h. dem Verhältnis von kolonisierten zu nicht kolonisierten Personen) [189], der Erregerdichte [190], dem Übertragungsweg [186,191] und dem Übertragungsziel [40, 186] sowie der Vorerkrankung des Empfängers [40,192].…”
Section: Definitionen/glossarunclassified
“…[2][3][4][5][6][7][8] Undetected MRSA-positive patients serve as reservoirs, and roommates of such patients and health care personnel are at significant risk of becoming colonized. [9][10][11][12][13] In addition, MRSA-positive persons contaminate the hospital's environment turning it into a reservoir for other patients. [14][15][16][17] After discharge from hospital, MRSA-positive patients may transmit their strain to their household members.…”
Section: Introductionmentioning
confidence: 99%